(untitled) (Research, Society and Development, 2020)
Backgroud: Low back pain (LBP) has been associated with severe impairments, primarily related to activities of daily living, functional ability and quality of life. A multimodal approach to pain management, such as transcranial direct current stimulation (tDCS) and peripheral electrical stimulation (PES), may improve outcomes in chronic LBP. However, the optimal cerebral target for stimulation still remains controversial. This pilot trial aims to investigate whether active stimulation could promote additional gains to the PES results in LBP patients. Our secondary objective is to investigate whether the stimulation of primary motor cortex and dorsolateral prefrontal cortex results in distinct clinical effects for the patients involved. Methods: Sixty patients with chronic low back pain will be randomized into one of three tDCS groups associated with PES: motor primary cortex, dorsolateral prefrontal cortex and sham stimulation. Each group will receive transcranial direct current stimulation at an intensity of 2 mA for 30 minutes daily for 10 consecutive days. Patients will be assessed with a Brief Pain Inventory (BPI), Roland Morris Disability Questionnaire (RMDQ), Medical Outcomes Study 36-item Short - Form Health Survey (SF-36) and electromyography at baseline, endpoint (after 10 sessions) and 1-month follow up. Discussion: This study will help to clarify the additive effects of tDCS combined with peripheral electrical stimulation on pain relief, muscle function and improvement in quality of life. Additionally, we will provide data to identify optimal targets for management of chronic low back pain.